(untitled) (Al-Mansour Journal, 2023)
The primary purpose of this study is to investigate the performance and residual strength of four reclaimed concrete one-way slabs. Three of the slabs were strengthened with near surface mounted carbon fiber reinforced plastic (NSM CFRP), and all of the slabs were presented in order to investigate the influence of various parameters on the structural behavior of each of the slabs. The experimental program consists of casting and evaluating a total of four samples, which are then separated into two primary categories. These groups were classified based on the manner in which they were loaded (monotonic, and modified repeated). Those slabs had a comparable shape and dimensions of 1200 mm by 600 mm by 140 mm. The experimental inquiry was expanded to include the study of many characteristics, such as the influence of increased CFRP strip thickness and the different types of loads on the maximum load capacity and load-deflection response. The results indicated that increase the added FRP strips area has a small effect on the cracked to ultimate load (???????????? / ???? ????) percent, where the percent of (???????????? / ???? ????) was 25 and 28 for reference slab without CFRP, and slab with CFRP of 1.2mm in thickness under monotonic load respectively, also adding CFRP strips has an effect on the ultimate load, the increase of adding CFRP strips area increased the failure load by about 3.1 for specimens slab with CFRP of 1.2mm in thickness with respect to the specimen reference slab without CFRP for monotonic load tests. The percent of ????u (slab with CFRP of 1.2mm in thickness under repeated loads) / ???? ???? (slab with CFRP of 1.2mm in thickness under monotonic loads) was 91.6 %. Adding CFRP strips has an effect on the cracking load in repeated load less than in monotonic load test, where the increase of adding CFRP strips area increased the cracking load by about 37.2% for slab with CFRP of 2.4mm in thickness with respect to the specimen slab with CFRP of 1.2mm in thickness under repeated load test. Repeated loads give crashing at the top fiber of slab, this is due to the effect of repeated loads which causes degradation of concrete stiffness and increased crashing of concrete.